The Novel of Six axes Robotic Arm for Industrial Applications - Rajendra R Aparnathi; Ved Vyas Dwivedi (Institute of Advanced Engineering and Science, 2014)
Automation technology is widely accepted and rapidly growing technology in the field of core and many other industries. Anyone can observe that due to these problems many industries are turning towards automaton. When searching for problem of labor manpower in middle-case industries, we came to know about many other things like production, speed of manufacturing and quality of the product are necessary in the current scenario. These parameters are not being well maintained in incorporate industries with manual manufacturing processes instead of using automatic system. Our objective is to solve these problems by efficient use of different technologies for making an industry fully or partially automated. By using technologies we can try to solve or reduce the effects of above problems.